Kidney Expression of Toll Like Receptors in Lupus Nephritis: Quantification and Clinicopathological Correlations. (21st August 2016) - Conti, Fabrizio; Spinelli, Francesca Romana; Truglia, Simona; Miranda, Francesca; Alessandri, Cristiano; Ceccarelli, Fulvia; Bombardieri, Michele; Giannakakis, Konstantinos; Valesini, Guido
Abstract : Objective . The study aimed at locating and quantifying Toll Like Receptor (TLR) 3, 7, 8, and 9 expression in kidney of patients with lupus nephritis (LN) and correlating them with clinicopathological features. Methods . Kidney sections from 26 LN patients and 4 controls were analyzed by immunohistochemistry using anti-human TLR3, TLR7, TLR8, and TLR9 polyclonal antibodies; the number of TLR-positive nuclei/mm 2 was evaluated on digitalized images. Results . Compared to controls, LN showed a significantly higher amount of glomerular and tubulointerstitial TLR9 (p = 0.003 andp = 0.007 ), whole and tubulointerstitial TLR3 (p = 0.026 andp = 0.031 ), and a higher tubulointerstitial TLR7 (p = 0.022 ). TLR9 positively correlated with activity index (p = 0.0063 ) and tubular TLR7 with chronicity index (p = 0.026 ). TLR9 positively correlated with Renal-SLEDAI (p = 0.01 ). Conclusions . This is the first study quantifying kidney expressions of TLRs in LN patients; the results show an overexpression of TLR3, TLR7, and TLR9 and demonstrate a correlation with clinicopathological indices supporting a role of these mediators in the pathogenesis of LN.